Structurally and environmentally favorable masonry units for infilled frames. (15th November 2018) - Markulak, Damir; Dokšanović, Tihomir; Radić, Ivan; Miličević, Ivana
Highlights: Challenge the idea of using structural types of masonry units as frame infill. Various mixtures of self-compacting concrete (SCC) are developed and tested. Key mechanical properties of masonry wallets made of designed SCC units are obtained. Tests confirmed low stiffness and strength combined with robustness and compactness. By using non-structural infill an engineer takes more active role in design. Abstract: Infill in frames can have detrimental or beneficial effects, and among parameters that influence interaction, infill type stands out as a common element. Masonry units utilized for masonry structures are also frequently utilized as a frame infill. Consequently, their higher strength and stiffness greatly influence the surrounding frame, which can often lead to undesired effects. Therefore, a different approach is proposed – designing a masonry unit with structurally favorable properties for an infill. Lower stiffness and strength of infill can generally benefit the structure as in comparison to a bare frame such infill provides stiffness, but has a higher potential to sustain enough damage to prevent significant detrimental effects on the frame. Out of plane stability, compactness and lightweight are favorable, which is necessary to combine with environmental aspects. To encompass favorable goals, a new masonry unit was developed, based on research of 13 self-compacting concrete mixtures with recycled materials in their composition. Utilizing recycled crushed brick and ground expanded polystyrene enabled reductions in weight, carbon footprint, stiffness and strength. Among various mixtures, based on key material properties, two were selected for production and further testing of masonry units. Units' density, stiffness and strength showed potential for application as non-structural infill. With a mortar mixture that showed favorable and reliable experimental results, masonry wallets were tested for compression strength and modulus of elasticity, which confirmed developed units potential. From available literature collected results of modulus of elasticity and compressive strength on masonry wallets indicate that developed units are very similar to AAC units, but with significant environmental advantages. Designed mixtures of self-compacting concrete with developed unit shape show great potential for use as non-structural infill, with highlighted positive interaction aspects of a frame-infill composite. This enables the engineer to take a more active role in design, by preventing detrimental effects through choice of constituents in a frame-infill composite.